SÍNTESE, CARACTERIZAÇÃO E ANÁLISES IN VITRO E IN VIVO DA TOXICIDADE DE NANOPARTÍCULAS DE FERRITE DE COBALTO PARA APLICAÇÕES BIOMÉDICAS - Fontanive, Verusca Cristina Pizzatto (2012)
Magnetic nanoparticles (NPs) are produced mainly from Fe3O4 (magnetite) and Fe2O3 (maghemite), as well as CoFe2O4 (cobalt ferrite), NiFe2O4 (nickel ferrite), among others. The NPs of cobalt ferrite (NPFC`s) have several possible applications in the biomedical field, among which stand out: the controlled release of drugs, contrast agents for magnetic resonance imaging, carriers of drugs guided by magnetic field treatment of tumors via hyperthermia, magnetic separation and biomolecular diagnostics. Front many possibilities for applying the magnetic NPs was developed by sol-gel modified synthesis NPFC`s with sizes between 30 and 100 nm. Characterizations were performed via X-ray diffraction, magnetic analysis, scanning electron microscopy and transmission electron microscopy. After these determinations were carried out in vitro with human blood cells using different concentrations of NPFC`s checking the possible cytotoxicity. The tests were polymorphonuclear leukocytes in feasibility (PMNL) and red blood cells, where there was no cytotoxicity on the cells in the presence of NPFC`s. The experiment was performed in vivo in mice, male and female, being orally administered a suspension of NPFC`s in different concentrations for seven days. Finally, samples were collected for measurement of creatinine, urea, alkaline phosphatase (ALP), aspartate aminotransferase (AST) and alanine aminotransferase (ALT), assessment of biochemical markers, in general, there were no significant changes that would show damage, except for changes in the levels of urea in the group of male mice. Were removed liver, kidney and spleen of the animals for histological evaluation in two cuts the kidney, the group of male mice that received the suspension NPFC`s, it was observed the formation of cistificação / dilation, however in the other analyzes organs no changes indicating significant damage. The results showed that the NPFC`s biocompatibility feature contributing to the evaluation of the possible use NPFC`s for the targeting of drugs.